Awareness of Normal Weight, Overweight and Obese Patients About Complications, Risk Factors and Prevention of Obesity - Ahmet Dirikoç; Birgül Genç; Didem Ozdemir; Şefika Burçak Polat; berna evranos ogmen; Oya Topaloğlu; Reyhan Ersoy; Bekir Cakir (Ankara Medical Journal, 2021)
INTRODUCTION: We aimed to determine the awareness of obese, overweight and normal-weight patients about the complications, causes and prevention of obesity. METHODS: Patients who were admitted to our clinic during a four months period were included. Demographical features, familial histories of obesity, smoking, alcohol use, chronic diseases, medications, medical nutrition therapy and exercise habits were questioned. Patients were divided into groups as normal, overweight and obese according to the WHO criteria. RESULTS: The median age of 352 patients was 45 (18-88), Of all, 282 (80.11%) were female, and 70 (19.89%) were male. Fifty-one patients (14.49%) were normal weight, 72 (20.45%) were overweight, and 229 (65.06%) were obese. The level of education was lower in obese patients, and the family history of obesity was higher (p<0.001). The percentage of patients who agreed that obesity was a risk factor for insulin resistance, type 2 diabetes, cardiovascular disease, hypertension, dyslipidemia, fatty liver, sleep apnea, asthma, gastrointestinal problems, depression and other mental problems, and death was changing between 65% and 92. Awareness of obesity risk factors was similar between groups. The rate of those who knew that eating 4-6 meals a day and not missing snacks was important for a healthy diet was highest in the obese group (p=0.043). DISCUSSION AND CONCLUSION: Although awareness of some obesity-related complications was high in our study, awareness of risks such as cholelithiasis, pancreatitis and cancer development was low. For the prevention and effective treatment of obesity, it is necessary to increase the level of awareness of the disease.